SISTEM INFORMASI ASMARA (ASPIRASI MASYARAKAT) DESA SEBAGAI DASAR PERENCANAN PEMBANGUNAN DESA BERBASIS WEB ANDROID DIMASA PANDEMI COVID 19 : STUDI KASUS DESA BOJONGKULON - Sokid Sokid; Agust Isa Martinus (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Information and communication technology (ICT) during the COVID-19 pandemic is very useful in assisting the implementation of the implementation of the Village Government, both in the formulation of Government policies that require input and community aspirations, implementation of development and reporting of activities that are known to the village community in a transparent manner so that there is an evaluation of future policy improvements over the basis for village community participation from various levels of society. Professional, efficient and effective Village Government, open, and responsible in accordance with the mandate of the Village Law Number 6 of 2014 with a policy formulation mechanism as mandated by Minister of Home Affairs 114 of 2014 and PermenDesa PDTT Number 17 of 2019 concerning General Guidelines for Development and Empowerment of Village Communities in general requires input and aspirations of the community which can be done by utilizing information technology as a medium for screening the aspirations of the community and participating in the implementation of the Village Government both directly and virtually so that the principles of implementing e-government can be carried out. In absorbing the aspirations of the Village community, it is necessary to have an information system that is easily accessible by the community as a forum for the aspirations of the Village community, the Village community can input their aspirations and input in writing by inputting their input according to the available menu by attaching supporting evidence in the form of photos and an explanation of the actual conditions in the field, as material for formulating village development plans. In this study, the author will make a prototype of an integrated village community information system where in the information system the community can participate in conveying aspirations as a basis in village development planning so that from the results of participation in development planning, village communities can enjoy information on village development, development good infrastructure for economic activities in the village, such as trading, farming and other activities, the community and the village government together empower the village's economic potential a with community empowerment and community development programs.